(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background: TORCH infections in pregnant women can result in serious effects, such as miscarriages, stillbirths, intrauterine growth retardations and congenital anomalies. TORCH infections caused by Toxoplasma gondii, rubella virus, cytomegalovirus and herpes simplex virus, and these organisms can transmit from mother to fetus through the placenta. The study aimed to investigate TORCH infection in pregnant women. Materials and Methods: A cross-sectional and analytical study was conducted on 268 pregnant women (21-45 years) with miscarriage history. Blood samples were taken from all participants for screening TORCH infection. The screening was performed via Cobas e411 and using ROCH test kits manufactured by ROCH Company, Germany. Results: Toxoplasma gondii was found in the highest percentage of TORCH infection (45.1%), followed by Cytomegalovirus CMV (21.6%), then Rubella (18.3%), which was found in the lowest percentage of infection. Non-significant differences were observed among age groups concerning Toxoplasmosis and Rubellosis, but significant differences were observed with CMV infection. Toxoplasma infections were observed with a high rate of infection (61.2%) in house wife, but there were no significant differences in Rubella and CMV infection based on occupation. The highest rate of toxoplasmosis (63.6%) was recorded in the first trimester of gestational age, with a significant difference, whereas there were no significant differences between gestational age with Rubella and CMV infections. Correlation was recorded between toxoplasmosis and the number of miscarriages with the highest rate (68.9%) in the number of miscarriages, whereas a non-significant correlation was recorded between Rubella or CMV infection and the number of miscarriages. Conclusions: In TORCH infection, Toxoplasmosis are observed in high rate (45.1%) among pregnant women suffered from previous miscarriages, and significant correlation between toxoplasmosis and the number of miscarriages was found but this correlation was non-significant with Rubella and CMV infection.